Jejunal motility during cyclic total parenteral nutrition in patients with Crohn's disease. Issue 6 (June 1989) - Ducrotte, P; Koning, E; Guillemot, F; Guedon, C; Lerebours, E; Denis, P; Colin, R
Abstract : Our aim was to study the jejunal motility (a) in seven patients receiving longterm (median: 24 days) cyclic total parenteral nutrition (CTPN) for an acute exacerbation of Crohn's disease involving the ileum and/or the colon without any sign of occlusion and (b) in six healthy volunteers undergoing the same parenteral nutrition for one day after an overnight fast. Continuous recordings, lasting 20 hours, were carried out in patients after correction of their nutritional status and significant improvement of the Crohn's disease activity index. In five of the seven patients, we recorded seven to 14 phase III episodes (PIII) (median: 10), both more frequent and slower during the nocturnal part of the recording time as compared with diurnal. Seven to 18 PIIIs (median: 12) were found in controls. The overall duration of the motor activity was not different between these five patients and controls. In the remaining two patients, no PIII episode was recorded and 79% and 57% respectively of the whole recording time consisted of irregular motor activity. Our work therefore, shows that: (a) PIIIs remain and have a circadian variation in their periodicity and propagation velocity, in most of our patients undergoing longterm CTPN (b) CTPN does not determine a longer duration of motor rest of the small bowel in patients than in controls submitted for a short period of time to the same parenteral intake.